A study in honor - O'Dell, Claire (Harper Voyager, an imprint of HarperCollinsPublishers, 2018)
Set in a near future Washington, DC, this novel offers a feminist twist on Sherlock Holmes, in which Dr. Janet Watson and covert agent Sara Holmes unmask a murderer.